ANALISIS KESIAPAN MASYARAKAT DESA DALAM MENGEMBANGKAN WISATA BENDUNGAN LAMA PAMARAYAN KABUPATEN SERANG - Maulana, Rachmat; Halim, Ibrohim Abdul; Salmande, Ali; Hakim, Agus Lukman (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2023)
The Tourism Village Around the Cultural Heritage of the Lama Dam and Kalimati Pamarayan has been established through a Decree of the Regent of Serang Year 2022. This research aims to look at the perceptions and readiness of stakeholders in the development of a tourism village. This research is descriptive in nature by conducting a survey of stakeholders around the Cultural Heritage of Bendungan Lama and Kalimati Pamarayan, Serang Regency, using quantitative descriptive analysis. The results of the research show that the people around the tourist village around the Bendungan Lama Cultural Heritage and Kali Mati Pamarayan have a high level of confidence that the area is very capable of being developed, with an average score of 8.97 out of 10. The results of an assessment conducted on nine aspects of the tourism village shows that the old dam area and Pamarayan dead river are in the category of fulfilling tourism feasibility. This research recommends the establishment of a joint institution and submitting a licensing process to BBWS C3 and BPCB so that the community can develop a Tourism Village